2021
DOI: 10.2174/1573405616666200406110547
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Detection and Classification using Traditional Computer Vision Techniques: A Comprehensive Review

Abstract: : Breast Cancer is a common dangerous disease for women. In the world, many women died due to Breast cancer. However, in the initial stage, the diagnosis of breast cancer can save women's life. To diagnose cancer in the breast tissues there are several techniques and methods. The image processing, machine learning and deep learning methods and techniques are presented in this paper to diagnose the breast cancer. This work will be helpful to adopt better choices and reliable methods to diagnose breast cancer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 73 publications
1
37
0
Order By: Relevance
“…It was observed that the entropies are efficiently used to analyse medical data, i.e., 1D signals and 2D signals [52][53][54][55]. Hence, seven entropies (10)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the entropies are efficiently used to analyse medical data, i.e., 1D signals and 2D signals [52][53][54][55]. Hence, seven entropies (10)…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the irregularities and complexities associated with varied shapes and sizes of haemorrhagic lesions with time will also make the process more difficult and strenuous. Moreover, the process can become a laborious and daunting task, particularly in large clinical settings, which can introduce inadvertent error and delay [10][11][12][13][14]. This can cause additional morbidity and even mortality to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…For the infected region, complete knowledge is essential, so that a relevant label is assigned. However, due to textural and color variations, the classification task becomes more complex [29] . However, deep methods came with the property of extracting relevant information, and also have a tendency to learn from the complex features.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Apart from leukaemia cancer, there are also some approaches developed for medical image for segmenting and detecting different cancers such as in [27–33]. The rest of this paper focuses on the extension and further refinement of the strategy of using digital image processing to increase the accuracy rate for ALL‐leukaemia cell detection.…”
Section: Literature Reviewmentioning
confidence: 99%